2016
DOI: 10.1590/1983-80422016243159
|View full text |Cite
|
Sign up to set email alerts
|

Ordem de não reanimar pacientes em fase terminal sob a perspectiva de médicos

Abstract: The do-not-resuscitate order is the explicit statement by patients with advanced disease in progression refusing cardiopulmonary resuscitation. This study aimed to describe the attitude of physicians in relation to the this order and the need for its regulation. A questionnaire was applied to 80 physicians in the medical bureau of the Regional Council of Medicine of Joacaba/SC, Brazil. It was found that 90% of the respondents knew the meaning of do-not-resuscitate, 86.2% agreed to respect it, 91.2% considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
6
0
6
Order By: Relevance
“…The reflection on this theme is not frequent in the literature. A previous study, conducted in the same region, showed that 10% of the physicians did not know the term 5 , showing that its approach by medical schools is not systematic. The lack of ethical and legal orientation is a factor that probably contributes to the lack of knowledge in Brazil, raising the need for regulation.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The reflection on this theme is not frequent in the literature. A previous study, conducted in the same region, showed that 10% of the physicians did not know the term 5 , showing that its approach by medical schools is not systematic. The lack of ethical and legal orientation is a factor that probably contributes to the lack of knowledge in Brazil, raising the need for regulation.…”
mentioning
confidence: 87%
“…The Carta dos Direitos dos Usuários da Saúde (Health Users' Rights Charter) 4 assured to the patients the right to choose the place of death, appointment of a representative and the possibility of refusing treatment. Concerning the order not to reanimate, there is no explicit official guideline in Brazil, but there are ethical 5 and legal 4 norms with the goal of preventing the practice of dysthanasia. In this context, the importance of investigating the perception of patients in relation to different aspects of health care arises, especially when there is no therapeutic possibility.…”
mentioning
confidence: 99%
“…In addition, it concludes that the moment is opportune to elaborate ethical guidance on the order not to reanimate in Brazil, which fills the current regulatory gap 13 .…”
Section: : Medicine Has Many Biases How Will I Protocol the Lsl?mentioning
confidence: 99%
“…However, it was pointed out the need to regulate the decision. Even in the case of progressive disease in terminal stage, it is important not to reanimate only upon request or family consent, although they agree that the physician should take part in the decision 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation